Language Assessment Literacy for Pre-service Teachers: Course Expectations from Different Stakeholders (GIST – Education and Learning Research Journal, 2018)
In the field of applied linguistics, for the past fifteen years, there have been discussions about language assessment literacy (LAL) —the knowledge, skills, and principles related to assessing language ability— (Davies, 2008; Fulcher, 2012). However, the field lacks research on the professional development of language teachers, particularly pre-service language teachers, through training in language assessment. Our paper focuses on the preliminary findings of an action research study whose goal is to identify the impact of a language assessment course for pre-service teachers in a language teaching program in a state university in Colombia. Data collection for the diagnostic stage of the action research cycle used a multiple-choice questionnaire for student needs and wants, an open questionnaire for professors, an interview with an expert, and researchers’ journals. Preliminary findings indicate that there is a need to combine theory and practice of language assessment, with an emphasis on current methodologies for language teaching, assessment in bilingual education, and local policies for assessment. The paper highlights recommendations and challenges when designing a language assessment course based on insights from existing literature and includes implications for professional development.
Keywords: Language assessment literacy; language testing; language policies; bilingual education